2021
DOI: 10.36849/jdd.5638
|View full text |Cite
|
Sign up to set email alerts
|

Intense Pulsed Light: A Methodical Approach to Understanding Clinical Endpoints

Abstract: Background: Intense Pulsed Light (IPL) is a non-coherent polychromatic broadband filtered flashlamp that emits light in the spectrum of approximately 400-1200 nm. Its effects on photorejuvenation are well documented. The goal of this study is to help practitioners better conceptualize and fine tune IPL device settings in order to produce the most effective and safest clinical outcome. Materials/Methods: This was a prospective study testing several filters (515 nm; 560 nm; 590 nm and 530-650; 900-1200 nm vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…12 This versatility contributes to the ability of IPL to address multiple target chromophores, at different locations on the skin, simultaneously. 1,7 On the other hand, such versatility implies reduced selectivity for the target chromophore 12 therefore, most IPL devices incorporate various cutoff filters that can eliminate wavelengths. 1 The selected wavelength, together with the precise pulse duration, will increase the selectivity in the photothermolysis process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This versatility contributes to the ability of IPL to address multiple target chromophores, at different locations on the skin, simultaneously. 1,7 On the other hand, such versatility implies reduced selectivity for the target chromophore 12 therefore, most IPL devices incorporate various cutoff filters that can eliminate wavelengths. 1 The selected wavelength, together with the precise pulse duration, will increase the selectivity in the photothermolysis process.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 There are numerous IPL devices on the market today, each with a unique set of parameters, so the efficacy and safety profile may not be consistent between devices. 7 The purpose of this study is to validate the safety and efficacy of a novel setting IPL device optimized to treat vascular and pigmented lesions in various areas of the skin.…”
mentioning
confidence: 99%
“…Multiple pulses can be given with variable pulse delays to reduce the side effects and prevent thermal damage, allowing sufficient skin cooling during the procedure. 3,4 Researchers have theorized that IPL therapy reduces Propionibacterium Acnes (P. acnes) in the skin and shrinks the size of the pilosebaceous unit and, subsequently, its function. 5,6 Previous literature has shown the efficacy of IPL for Acne vulgaris ranging from 34% to 88% in both inflammatory and non-inflammatory acne.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, histological analysis has shown that the dermal heat generated by IPL treatments induces new collagen production, potentially resulting in improved skin texture. 7,8 By utilizing certain wavelengths, pulses, and fluences, numerous skin conditions can be effectively treated with IPL. The optimal wavelength varies depending on its penetration depth, tissue interactions, and the target chromophore.…”
mentioning
confidence: 99%
“…Choosing the most suitable wavelength range can be facilitated by the use of cutoff filters. 7,9,10 Pulse width modification is a new advancement in lasers and IPL to improve energy distribution. Conventional pulse distribution delivers energy unevenly, while new technologies aim for uniform energy delivery.…”
mentioning
confidence: 99%